2014
DOI: 10.1128/jvi.00464-14
|View full text |Cite
|
Sign up to set email alerts
|

Animal Model of Respiratory Syncytial Virus: CD8 + T Cells Cause a Cytokine Storm That Is Chemically Tractable by Sphingosine-1-Phosphate 1 Receptor Agonist Therapy

Abstract: The cytokine storm is an intensified, dysregulated, tissue-injurious inflammatory response driven by cytokine and immune cell components. The cytokine storm during influenza virus infection, whereby the amplified innate immune response is primarily responsible for pulmonary damage, has been well characterized. Now we describe a novel event where virus-specific T cells induce a cytokine storm. The paramyxovirus pneumonia virus of mice (PVM) is a model of human respiratory syncytial virus (hRSV). Unexpectedly, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 42 publications
3
49
0
Order By: Relevance
“…S1PR1 expression in pDCs and its functional coupling to turnover of IFNAR1 and STAT1 down-modulation may reflect an evolutionary pathway suited to therapeutic exploitation. We have shown that S1PR1 agonism protects from influenza and mouse pulmonary virus immunopathology while allowing full development of sterilizing immunity, neutralizing Abs, and quantitatively normal immunological memory (10,(20)(21)(22)(23). Thus, blunting, but not abolishing, IFN-I amplification by the S1P/S1PR1 signaling axis allows host defense from pathogens.…”
Section: Significancementioning
confidence: 94%
“…S1PR1 expression in pDCs and its functional coupling to turnover of IFNAR1 and STAT1 down-modulation may reflect an evolutionary pathway suited to therapeutic exploitation. We have shown that S1PR1 agonism protects from influenza and mouse pulmonary virus immunopathology while allowing full development of sterilizing immunity, neutralizing Abs, and quantitatively normal immunological memory (10,(20)(21)(22)(23). Thus, blunting, but not abolishing, IFN-I amplification by the S1P/S1PR1 signaling axis allows host defense from pathogens.…”
Section: Significancementioning
confidence: 94%
“…We and others have explored inflammatory responses to and immunomodulatory control of respiratory virus infection using the pneumonia virus of mice (PVM) model of acute pneumovirus infection (Dyer et al , 2012; Bondue et al , 2011; Walsh et al , 2014; Scheer et al , 2014; Siegle et al , 2011). PVM is closely related to RSV; however, unlike RSV, PVM undergoes robust replication in vivo , most prominently in bronchial epithelial cells of inbred strains of mice.…”
Section: Introductionmentioning
confidence: 99%
“…The product of SK activity, S1P, can have intracellular signalling functions or be secreted from cells to act on cell surface S1P receptors (Leclercq & Pitson, 2006;Rosen et al, 2014;Spiegel & Milstien, 2011;Xia & Wadham, 2011). A number of studies have shown that modulating the S1P/receptor can reduce virus-induced disease and tissue injury associated with IAV (Marsolais et al, 2009;Walsh et al, 2011) and in an animal model of RSV infection (Walsh et al, 2014). Thus, studies of the SK-virus interaction are of significant interest to potential therapeutic interventions for viral diseases.…”
Section: Introductionmentioning
confidence: 99%